Exploring Abizard's Early Language Acquisition: A Case Study in Javanese Language - Asroriyah, Atik Muhimatun; As’adiyah, Cindyana Mauludi Hafidz (Yayasan Kyadiren, 2022)
This study analyzes the language development of a three-year-old child, Abizard Naufal Muttaqin, focusing on phonological, morphological, and semantic aspects. Data is collected through observation and video recording using a descriptive qualitative research approach. The study shows that Abizard's language development is typical for his age, with notable progress in phonological and morphological skills. However, his semantic skills require further development. Effective strategies for supporting language learning in early childhood are provided, such as reading to children, encouraging verbal communication, and providing a rich language environment. The study emphasizes the importance of supporting language development in early childhood and contributes to the existing knowledge on language acquisition. Parents and educators can use these findings to help children develop their language skills.